Does relative income matter for the very poor? Evidence from rural ethiopia - Alpaslan Akay; Peter Martinsson (Institute for the Study of Labor (IZA), 2008)
We studied whether relative income has an impact on subjective well-being among extremely poor people. Contrary to the findings in developed countries, where relative income has shown a significant and negative impact on subjective well-being, we cannot reject the hypothesis that relative income has no impact on subjective well-being in rural areas of northern Ethiopia.
urn:nbn:de:101:1-20081127328
Keywords: D10; 330; Absolute income; relative income; subjective well-being; Ländliche Armut; Einkommensverteilung; Nutzen; Lebenszufriedenheit; Äthiopien